(untitled) (Anwer Khan Modern Medical College Journal, 2017)
Background: Laparoscopic cholecystectomy is an accepted alternative to open cholecystectomy. This study was aimed to compare the results of laparoscopic and open cholecystectomy with respect to duration of operation, complications, hospital stay and cost. Materials and Methods: This was a prospective type of study. 200 patients of gallstone disease were randomly selected. 100 patients underwent laparoscopic cholecystectomy and 100 underwent open cholecystectomy from July 2014 to June 2015 in surgery units of Jahurul Islam Medical College Hospital. Data regarding age, sex, operation time, complications, hospital stay and total cost were collected from patient and from hospital record. Then we compared the data of laparoscopic and open cholecystectomy. Results: We found that mean operating time for laparoscopic cholecystectomy was 45 minutes and for open cholecystectomy was 60 minutes.There is no significant difference in incidence of complications between open and laparoscopic procedure. In our study, mean postoperative hospital stay for laparoscopic surgery was 3.5 days and in open cholecystectomy was 6 days. In this study total cost of laparoscopic surgery is less than open surgery though operation team charge is more in laparoscopic surgery. Conclusion: Laparoscopic cholecystectomy is a safe and cost effective alternative to open cholecystectomy. Anwer Khan Modern Medical College Journal Vol. 7, No. 1: Jan 2016, P 20-22